Trajectory of COVID-19 vaccine hesitancy post-vaccination and public's intention to take booster vaccines: A cross-sectional analysis - Muhammad Salman; Tauqeer Hussain Mallhi; Yusra Habib Khan; Zia Ul Mustafa; Muhammad Tanveer Khan; Faiz Ullah Khan; Muhammad Hammad Butt; Naureen Shehzadi; Muhammad Junaid Farrukh; Maria Waheed; Fatima Azmat; Areej Saeed; et al. (Taylor & Francis Group, 2023)
Vaccine hesitancy (VH) is not a new phenomenon in Pakistan and is regarded as one of the primary causes of unsatisfactory vaccination campaigns. This study determined post-vaccination COVID−19 VH, factors influencing COVID−19 vaccine uptake, and public's intent to receive booster vaccinations. A cross-sectional study was conducted among adult population of Lahore, Pakistan. Participants were recruited via convenience sampling between March and May 2022. SPSS version 22 was used for the data analysis. A total of 650 participants were included in the study (age = 28.1 ± 9.7 years; male-to-female ratio nearly 1: 1). The majority of participants received Sinopharm followed by Sinovac vaccine. The top three reasons of vaccine uptake were "only vaccinated individuals are allowed at the workplace, and educational institutes" (Relative importance index (RII) = 0.749), "only vaccinated people are allowed to go to markets, malls and other public places" (RII = 0.746), and "protect myself from the infection" (RII = 0.742). The mean COVID−19 VH score was 24.5 ± 6.2 (95% CI 23.9-24.9), with not being pro-vaccines and poor economic status were the significant predictors of COVID−19 vaccine hesitancy among immunized individuals (p < .05). Acceptance of booster vaccines was negatively associated with younger age and a lower level of education. Furthermore, being pro-vaccine was associated with a greater likelihood of accepting booster vaccines (p = .001). The Pakistani public continues to express VH toward COVID−19 vaccines. Therefore, aggressive measures must be taken to combat the community factors that contribute to it.